Chiharu Shiota the hand lines (Actar Publishers, 2014)
Shiota's installations produce their own spaces, where hundreds of invisible threads that bond us to things can be seen. In these domestic scenarios she proposes, threads become bridges between a bride's dress and the absent subject, a piano, suitcases and a mirror. In her work, these threads are veins with tears, fear for abyss, life and death; threads that are plots of particular and universal stories, interweaving like the inverted roots of a tree, just like a rhizome through multiple branches that hold up the relationship between she and the world. The threads that transport the information and are essential in all the communication, but at the same time make up networks or wire fences that hold up the way to strangers in kinds of spaces where everyday life is in conflict with desired production.